Higher education for the people : critical contemplative methods of liberatory practice - Krikorian, Maryann (Research on stress and coping in education series., 2022)
"This monograph aims to uncover value-belief-systems underlying dominant narratives in modern IHEs, impacting the lives of many multidimensional adult learners. To do so, Eurocentrism and neoliberalism are used to analyze the socio-cultural-political movements of the U.S. and its influence on higher education trends. Then, models of adult consciousness and transformative approaches to adult learning are introduced to problematize dominant narratives and make the case for more complex epistemologies. With critical contemplation, acts of compassion for interdependence, self-compassion for intentionality, authentic relationships for political consciousness, listening for non-duality, and mindfulness for impermanence (CALM) are introduced as ways to emphasize self-transformation and self-actualization. CALM practice is just one way to join others in the social justice work of wholeness and humanity to better support multidimensional adult learners. Along with this understanding comes the potential to disrupt dominant narratives with a moral stance, honoring innate human value and the diverse human condition. The future of institutions of higher education must be guided by a moral position in the name of healing and wellness. Together, we can transform higher education so that institutions are a place where adult learners create the conditions of freedom to actualize the right to self-worth, the liberty to connect with others, and the pursuit of personal fulfillment, honoring this nations guiding principles of life, liberty, and happiness."--